Tailored PVDF nanocomposite membranes using exfoliated MoS2 nanosheets for improved permeation and antifouling performance - Sri Abirami Saraswathi, Meenakshi Sundaram; Rana, Dipak; Vijayakumar, Prabu; Alwarappan, Subbiah; Nagendran, Alagumalai (New journal of chemistry, 2017)
Exfoliated molybdenum disulfide (E-MoS 2 ) nanosheets were synthesized from bulk MoS 2 . Poly(vinylidene fluoride) (PVDF) was incorporated into E-MoS 2 to yield nanocomposite ultrafiltration (UF) membranes by the phase inversion technique. Various proportions of E-MoS 2 (0.1, 0.5 and 0.8 wt%) were prepared and were characterized in terms of permeation and antifouling properties. FT-IR and XRD studies confirmed the presence of E-MoS 2 in the membranes. Moreover, SEM and FESEM/EDX analysis of the membranes confirmed the increase in the porosity and presence, respectively, of E-MoS 2 . Atomic force microscopy (AFM) images confirmed that the membrane with 0.5 wt% E-MoS 2 exhibited a uniform surface structure with ( R a = 35 nm), compared to the pure PVDF membrane ( R a = 37.6 nm). In addition, the membrane with 0.5 wt% E-MoS 2 , exhibited higher pure water flux (PWF) (105.1 L m −1 h −1 ), water content (73.7%), porosity (12.24%), bovine serum albumin (BSA) solute rejection (92.3%), least mechanical stability (1.13 MPa), hydraulic resistance (7.44 kPa L −1 m −2 h −1 ) and contact angle (72.8°). From all these, it is evident that the overall PVDF membrane performance was enhanced by the E-MoS 2 addition, and the membrane with 0.5 wt% E-MoS 2 outperformed the other counterparts due to its versatile characteristics and superior potential in the water treatment. Exfoliated molybdenum disulfide (E-MoS 2 ) nanosheets were synthesized from bulk MoS 2 .